Oscillations of Offshore Wind Turbines undergoing Installation I: Raw Measurements - Sander, Aljoscha (Zenodo, 2020)
Overview This repository contains data from an offshore measurement campaign conducted during the installation of the offshore wind farm trianel wind farm borkum II (https://www.trianel-borkumzwei.de/). The wind farm consists of 32 Senvion 6XM152 turbines. The installation took place between August 2019 and May 2020. An offshore wind turbine undergoing installation is interesting from a research point of view for several reasons: Simple geometry: turbine foundation and tower are both rotationally symmetric steel tubes. Rotational symmetry also leads to (approximate) isotropical structural characteristics in the plane normal to tower and foundation. High Reynolds number flow: Assuming a tower diameter of 6 m, and average wind speeds ranging from 5 m/s to 12 m/s under installation conditions, Reynolds numbers range from 4.5 million to 10.5 million. Wave loading under full-scale conditions. Practical relevance to improving the competetivity of offshore wind. For fluid mechanics, closely monitoring offshore wind turbines under wind and wave loading thus compares to a full-scale experiment. Monitoring 32 turbines undergoing installation thus enables the measurement a broad spectrum of different states. The investigation into the data is ongoing, questions and contributions are welcome. The current data release still does not include all data. The dataset will thus be updated again in the future with more data to come. First analytic results can be found here: Sander, A, Haselsteiner, AF, Barat, K, Janssen, M, Oelker, S, Ohlendorf, J, & Thoben, K. "Relative Motion During Single Blade Installation: Measurements From the North Sea." Proceedings of the ASME 2020 39th International Conference on Ocean, Offshore and Arctic Engineering. Volume 9: Ocean Renewable Energy. Virtual, Online. August 3–7, 2020. V009T09A069. ASME. <https://doi.org/10.1115/OMAE2020-18935> Sander, A, Meinhardt, C & Thoben, KD. "Monitoring of Offshore Wind Turbines under Wind and Wave Loading during Installation" Proceedings of the EuroDyn 2020 XI International Conference on Structural Dynamics. Volume 1. Virtual, Online. November 23-26, 2020. <https://generalconferencefiles.s3-eu-west-1.amazonaws.com/eurodyn_2020_ebook_procedings_vol1.pdf> Recordings of the conference presentations are available on youtube: OMAE20: https://www.youtube.com/watch?v=QcAwdv6Z4e4 EURODYN20: https://www.youtube.com/watch?v=iL-jAe0luTw Physical Background An offshore wind turbine under installation conditions can be simplified as a cantilevered beam (circular cross-section, rotationally symmetric wall thickness) with an eccentric mass (nacelle with generator) vibrating transversally (fore-aft and side-side in the reference system of the nacelle) under wind and wave loads. Both wind and wave loads are stochastic and are described using statistical models. Wave loads are a function of the sea state. For a sea state, the most important parameters are significant wave heigh H_m0 and Wave peak period T_P. To a lesser extend, wave direction, zero upcrossing period and maximum wave height are also important. Different statistical models can be used to describe the sea state and the relationship between significant wave heigh H_m0 and wave peak period. Most prominent in the North Sea is the JONSWAP spectrum. Wind loads are depending on wind speed, wind direction, shear factor and turbulence intensity. Different statistical models are available to describe the wind spectrum. Wind and wave loads trigger a structural response of the turbine. The structural response depends on the loading spectrum as well as the transfer function. Furthermore, the structural response is strongly depending on the damping and elasticity of the structure. In turbines, damping is typically very low (~ 0.5 - 1.5 %). The response is dominated by the first Eigenfrequency of the turbine. As the turbine is assumed to be rotationally symmetric, the fore-aft and side-side mode are extremely close together if not indistinguishable [1]. The response has the characteristics of a narrow-band random vibration. A narrow-band random vibration is characterized by being dominated by a single, narrow frequency peak (here: first Eigenfrequency). The amplitude envelope follows a Rayleigh distribution and the phase angle is equally distributed between 0 and 2 pi. If viewed from above, the structural response describes a closed curve (orbit) which can be characterized by it shape (eccentricity), mean amplitude and direction. Mathematically speaking, this is a lissajous-figure, where the time series from one response direction is plotted as a function of the time series of the second response direction. [1]: under installation condition Experimental Setup Several locations were used to record data during the installation of the wind farm. They are listed in the following table: helihoist-{1,2}: data recorded from the helicopter hoisting platform atop the turbine nacelle. For most installations, two sensor boxes were deployed to ensure data availability. tp: Measurements from the transition piece sbitroot: Measurements from the blade lifting yoke's blade root side. The Z-axis is aligned to the blade main axis, X-Axis is perpendicular. sbittip: Measurements from the tip side of the blade lifting yoke. Z-axis aligned with the blade main axis, X-axis perpendicular damper: Measurements from the tuned mass damper used during single blade installation towertop: measurements from inside the turbine tower at the upper lift plattform towertransfer: measurements from atop the towers during sail out from the base harbour to the installation site Organization of data For each turbine installation, a separate folder can be found, e.g. turbine-01 for the first and turbine-16 for the 16th turbine. Turbine numbering follows the order of installation. Different data sources are organized in subfolders for each turbine dataset. Unfortunately, not every data source is available for each turbine. Data sources are roughly sorted into categories. The following table lists these categories: location / tom : data from custom build sensor boxes. Data includes acceleration, angular acceleration, magnetic field, gnss recording and rough estimates of the eulerian angles. waves / wmb-sued : Sea state statistics for the installatin period of the turbine. waves / fino : Sea state statistics from the german research platform FINO1 located approx. 6 km from the installation site. waves / waveradar : Sea state statstics, recorded by a wave rider wave laser. wind / lidar : high fidelity wind data recorded on the installation vessel during the installation of the wind farm. wind / scada : 10 min. mean wind statistisc recorded on wind turbines in the vicinity of the installation site. This data is used in case no LIDAR data is available. wind / anemometer : During some of the installations, anemometers were present on the installation vessel. These recordings are sorted into this sub-subfolder. wind / fino : Additonal wind statistics recorded by the FINO research station. Least recommended for investigations, as these recordings were taken approx. 6 km from the installation site. The zenodo data set includes 16 zip archives (for 16 turbines) as well as one zip archive including environmental data. The following lists the folder structure of the turbine-04.zip archive (with most of the data files removed for clarity). └── turbines ├── turbine-04 │ ├── helihoist-1 │ │ └── tom │ │ └── clean │ │ ├── turbine-04_helihoist-1_tom_clean_2019-09-01-11-27-17_2019-09-01-11-54-00.csv │ │ ├── turbine-04_helihoist-1_tom_clean_2019-09-01-11-54-00_2019-09-01-12-20-44.csv │ ├── sbitroot │ │ └── tom │ │ └── clean │ │ ├── turbine-04_sbitroot_tom_clean_2019-09-07-06-48-53_2019-09-07-07-17-16.csv │ │ ├── turbine-04_sbitroot_tom_clean_2019-09-07-07-17-16_2019-09-07-07-45-59.csv │ ├── towertop │ │ └── tom │ │ └── clean │ │ ├── turbine-04_towertop_tom_clean_2000-01-06-18-55-52_2000-01-06-20-30-10.csv │ │ ├── turbine-04_towertop_tom_clean_2000-01-06-20-30-11_2000-01-06-22-04-31.csv │ ├── towertransfer │ │ └── tom │ │ └── clean │ │ ├── turbine-04_towertransfer_tom_clean_2019-08-31-03-11-53_2019-08-31-04-00-09.csv │ │ ├── turbine-04_towertransfer_tom_clean_2019-08-31-04-00-10_2019-08-31-04-48-19.csv │ └── tp │ └── tom │ └── clean │ ├── turbine-04_tp_tom_clean_2019-08-31-18-34-45_2019-08-31-19-07-52.csv │ ├── turbine-04_tp_tom_clean_2019-08-31-19-08-00_2019-08-31-19-40-43.csv The following list the contents of the environment.zip archive. Note that again most of the data files have been removed for clarity. └── environment ├── waves │ └── wmb-sued │ ├── wmb-sued_2019-08-15.csv │ ├── wmb-sued_2019-08-16.csv │ ├── wmb-sued_2019-08-17.csv └── wind └── lidar ├── lidar_2019-08-03.csv ├── lidar_2019-08-04.csv ├── lidar_2019-08-05.csv TOM data description The abbreviation TOM referes to Tower Oscillation Measurement and the data that was acquired using a specific set of sensor boxes built by university of Bremen for this specific purpose. These Sensor Boxes were initially designed to measure accelerations and GPS tracks of offshore wind turbine towers undergoing installation. During the installation of the wind farm Trianel Windpark Borkum II they were subsequentially used to track the complete installation with a focus on single blade installation Data from the TOM devices comes as CSV files. The firmware of the boxes was designed, such that data was written into 10 MB sized txt files instead of one large txt file in order to circumvent data corruption due to power loss. However, this leads to a few milliseconds of missing data between log files. Additionally, jitter due to IO-Operations is present in the data as well and data should under all circumstance be resampled befor further analysis. Parameters provided by the TOM devices are listed in the following: epoch : machine readable time stamp based on the unix epoch in UTC [s] runtime : time since last boot of the tom device [ms] latitude : Degrees latitude in decimal writing. For Trianel: [degree due North] longitude : Degrees longitude in decimal writing. For Trianel: [degree due East] elevation : elevation above mean sea level [m] rot_{x,y,z} : Rotational acceleration around the three cartesian axis {x,y,z} of the TOM box. [degree / s^2] acc_{x,y,z} : linear acceleration in each of the three cartesian axis {x,y,z} in the reference system of the TOM box [m/s^2] mag_{x,y,z} : magnetic field strength in each of the local cartesian TOM box axis {x,y,z} [micro-Tesla] roll : eulerian roll angle (angle around the x Axis of the tom box) [degree] pitch : eulerian pitch angle (angle around the y Axis of the tom box) [degree] yaw : eulerian yaw angle (angle around the z Axis of the tom box) [degree] LIDAR wind data description A Leosphere WindCube LIDAR was mounted on the installation vessel Taillevent to record the atmospheric boundary layer during installation. The data recorded by the lidar was exported as csvs and provided by the vessel operator. The raw data includes the following parameters epoch : time stamp as a unix epoch in UTC [s] wind_speed_N : The wind speed at the N'th return level [m/s] wind_dir_N : Wind direction at the N'th return level in the vessels reference frame [degree] wind_dir_N_corr : Wind direction at the N'th return level due North [degree due North] heigh_N : The height of the lidar return level [m] Data is resampled to a 1 s return interval. wave data description Wave data was recorded using a waverider wave buoy (DWR-G). The wave rider buoy was located at 54 00' 238'' degree North and 6 26' 553'' degree East. In decimals: 54.0031096 North, 6.4425532 East. Based on the raw data, sea state statistics were derived with a return period of 30 minutes. The data comes as csv, column oriented text files. The first line entails parameter names and units and is commented out by a hashbang (unix commentary). The data is a combination of two different data files as provided by the buoy: \*.HIS Data Text File (History of Spectrum parameters) and \*.HIW Data Text File (History of Wave Statistics). This results in the two timestamps in the data file because history of wave statistics data is available immediately after each measurement time period, whereas history of spectrum parameters take approx. 5 minutes to calculate by the buoy and thus have a slightly later time stamp. For actual postprocessing purposes, a third timestamp rounded to full half hour is used. Parameters included in the data files are: epoch: number of seconds since 1st of January 1970 in UTC. Common time stamp format in computing. [s] Tp Tp := 1 / fp, peak period, the frequency at which S(f) is maximal [s] Dirp peak direction, the direction at f = fp [deg due North] Sprp peak spread, the directional spread at f = fp [s] Tz Tz := sqrt(m0 / m2), zero-upcross period [s] Hm0 Hm0 := 4*sqrt(m0), the significant waveheight [m] TI TI := sqrt(m[-2] / m0), integral period [s] T1 T1 := m0 / m1, mean period [s] Tc Tc := sqrt(m2 / m4), crest period [s] Tdw2 Tdw2 := sqrt(m[-1] / m1) [s] Tdw1 Tdw1 := sqrt(m[-1,2] / m0) [s] Tpc Tpc := m[-2] * m1 / m0 ^ 2, calculated peak period [s] nu nu := sqrt((T1 / Tz) ^ 2 - 1), band width parameter [-] eps eps := sqrt(1 - (Tc / Tz) ^ 2), bandwidth parameter [-] QP QP := 2 * m[1,2] / m0 ^ 2, Goda's peakedness parameter [-] Ss Ss :=2 * pi / g * Hs / Tz ^ 2, significant steepness [-] TRef TRef, reference temperature (25deg) [C] TSea TSea, sea surface temperature [C] Bat Bat, battery status (0..7) m[n] m[n] := Integral from f=0 to f=Inf over S(f) * f ^ n m[n,2] m[n,2] := Integral from f=0 to f=Inf over S(f) ^ 2 * f ^ n Percentage Percentage of data with no reception errors [%] Hmax Height of the highest wave [cm] Tmax Period of the highest wave) [s] H(1/10) Average height of 10% highest waves [cm] T(1/10) Average period of 10% highest waves [s] H(1/3) Average height of 33% highest waves [cm] T(1/3) Average period of 33% highest waves [s] Hav Average height of all waves [cm] Tav Average period of all waves) [s] Eps bandwidth parameter #Waves Number of waves Note: the m's are moments of the power spectral density S(f). : {"references": ["Sander et al. (2020a): RELATIVE MOTION DURING SINGLE BLADE INSTALLATION: MEASUREMENTS FROM THE NORTH SEA in International Conference on Ocean, Offshore and Arctic Engineering, Florida, USA", "Sander et al. (2020b): MONITORING OF OFFSHORE WIND TURBINES UNDER WAVE AND WIND LOADING DURING INSTALLATION in EuroDyn 2020, Athens, Greece"]}